İsviçre Borçlar Kanunu 2020 Tasarısı’nda Aşırı Yararlanma ve İrade Sakatlığı Hükümlerinin Düzenlenişi ve Türk Borçlar Kanunu ile Karşılaştırılması_x000D_ - (:unkn) unknown (My University, 2019)
Önemle belirtmek gerekir ki, gerek 818 sayılı Borçlar Kanunu gerekse 6098 sayılı Türk Borçlar Kanunubüyük ölçüde İsviçre Borçlar Kanunundan esinlenerek yürürlüğe girmiştir. Özellikle, 818 sayılı BorçlarKanunu hükümleri ile İsviçre’de yürürlükte olan Borçlar Kanunu hükümleri neredeyse aynıdır. Buyüzden İsviçre Borçlar Kanunu mehaz kanunumuz olarak da nitelendirilmektedir. İsviçre’de kanunkoyucu değişen sosyal ve ekonomik ihtiyaçları ve mevcut Borçlar Kanunu’nun uygulamada yarattığısorunları dikkate alarak İsviçre Borçlar Kanunu 2020 Tasarısını tartışmaya açmıştır.Çalışmamızda, İsviçre Borçlar Kanunu 2020 Tasarısında “Aşırı yararlanma” ve “İrade sakatlığı”hükümlerinin düzenlenişi ve Türk Borçlar Kanunu ile karşılaştırılması konuları ele alınacaktır.

It is crucial to state that, either 818 numbered Turkish Code of Obligations or 6098 numbered Turkish_x000D_ Code of Obligations became effective with the considerable effect of Swiss Code of Obligations._x000D_ The provisions of 818 numbered Turkish Code of Obligations and the provisions of Swiss Code of_x000D_ Obligations are almost same. Accordingly, Swiss Code of Obligations is known as a referred code._x000D_ Legislator of Swiss considered the changing social and economic demands and problems in practice_x000D_ and decided to bring up the issue of 2020 Draft of the Swiss Code of Obligations for discussion._x000D_ In our paper, unfair advantage and failure of intent provisions under 2020 Draft of the Swiss Code of_x000D_ Obligations and comparison of such provisions with Turkish Code of Obligations will be examined.
Regulations of Unfair Advantage and Failure of Intent Provisions under the 2020 Draft of the Swiss Code of Obligations and The Comparison of such Regulations with Turkish Code of Obligations